The teaching aids in the Biology-Chemistry Career - Amil Sellés, Yissel Pérez de Villa; Angarica García, Luisvis (Revista Minerva, 2020)
At the University of Pedagogical Sciences "Conrado Benítez García", in the Biology-Chemistry career in the 2010-2011 academic year, the use of teaching aids in the different subjects has been a necessity for the improvement of the teaching-educational process. The purpose of this research is to update knowledge on the subject and generate critical debate from positions that identify the teaching of Biological and Chemical Sciences in Cuba, having as a starting point the principles of Marxism-Leninism, Martianos-Fidelistas and Pedagogicos- Scientists, as well as the processes that occur in nature and its sustainable development. The results indicate that the use of different teaching means, whether technical or technological, related to the general objectives of the different disciplines and those of the professional model are intended for the comprehensive professional preparation of future graduates. Demonstrating satisfactory results in the teaching of this science and in improving the quality of the different forms of class organization in higher education.
Keywords: Teaching medium; Chemistry and Biology career